DESIGN OF SEMI-AUTOMATIC ONION FRYING MACHINE EQUIPPED WITH TEMPERATURE, TIMER, SPEED CONTROL - Umaroh, Susi Tri; Khofi, Muhammad Ichsan; Huda, Khoirul; Purnomo, Ahmad Setyo; Alfianti, Amalia Forma (AIBPM Publisher, 2018)
The purpose of this study is to provide solutions to existing problems in SME Fried Onion in Sidoarjo Region on the process of frying still conventional. The method used is to utilize technology TTS (Temperature, Timer, Speed Control) on the onion parser to produce fried onions with good quality and stable cooking temperature. The expected result is to improve the quality of fried onion productivity up to twice which initially only able to fry onion as much as 2 kg, can become 4 kg in one process of frying